Types of Qualitative Research - Muhammad Shohibuddin; Halimatus Sa’diyah (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
Types of qualitative research offer various approaches that can be tailored to the research objectives. The purpose of this study is to identify the different types of qualitative research and provide example titles for each type. The results of this study are as follows: The types of research commonly used in qualitative research include; case studies, descriptive studies, action research, phenomenology, ethnography, grounded theory, historical research, and hermeneutics. Ethical considerations in research include: honesty, objectivity, integrity, meticulousness, precision, verification, respect, social responsibility, trustworthy publication, competence, and legality.